STUDI KARAKTERISTIK LASAN ALUMUNIUM 6061-T6 DENGAN BERBAGAI METODE PENGELASAN - Josua Simaremare; Suprianto Suprianto (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Tungsten inert gas (TIG) and Metal inert gas (MIG) welding have been used to join varying materials; however, shielded metal arc Welding (SMAW) is rarely used for aluminum. This study aims to investigate the weld quality by using three welding methods for joining aluminum 6061-T6. The Welding process was carried out using a welding machine combination with an AWS electrode: E4043, filler consisting of ER 4043 0.8 and ER 4043. Defect inspection was performed using Dye Penetrant Check, Vickers hardness test, and tensile strength were carried out at room temperature. Visual observation of the microstructure at the weld and heat-affected zone (HAZ) areas with 200x magnification by using an optical microscope. The result shows more defects formed with SMAW in comparison with the TIG and MIG methods. The highest hardness, 63.8 HV, was achieved at the HAZ area, and a tensile strength of 195.4 MPa was obtained using the MIG technique. Microstructural observations reveal that the transformation in the HAZ area resulted in flat and coarse-grained structures.